2015
DOI: 10.1002/jppr.1094
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of job satisfaction amongst pharmacists in Malaysian public hospitals and healthcare clinics

Abstract: Background: For the past 10 years, the pharmacist workforce in Malaysia has experienced radical changes in demography, job scope and expectations as well as remuneration due to a drastic surge in the number of pharmacists employed in the public sector. Aim: To investigate the level of job satisfaction amongst pharmacists working in the public sector in Malaysia. Methods: A cross-sectional survey was conducted amongst registered pharmacists working in three of the most populated states in Malaysia. A validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 17 publications
7
36
4
Order By: Relevance
“…In the present study, age and years of experience in practicing community pharmacy had a positive effect on stress levels. Similarly, a study by Manan et al . among Malaysian pharmacists working in the public sector also found significant differences in job satisfaction with age and length of service.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, age and years of experience in practicing community pharmacy had a positive effect on stress levels. Similarly, a study by Manan et al . among Malaysian pharmacists working in the public sector also found significant differences in job satisfaction with age and length of service.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, age and years of experience in practicing community pharmacy had a positive effect on stress levels. Similarly, a study by Manan et al 18 among Malaysian pharmacists working in the public sector also found significant differences in job satisfaction with age and length of service. In the present study, pharmacists aged between 25 and 44 years and having <15 years experience tended to have higher stress than pharmacists who were aged ≥55 years with >20 years work experience.…”
Section: Stress Levels Among Community Pharmacistsmentioning
confidence: 76%
See 2 more Smart Citations
“…While pharmacists become increasingly important as part of the healthcare system globally, performance‐based remuneration and rewards have been identified as a major motivator in their careers . The utilization of pharmacists’ clinical knowledge and skills, flexible job descriptions and due recognition for their good work performance were also shown to have a positive impact on their job satisfaction . On the other hand, inadequate job‐related training was consistently perceived by pharmacists as one of the major challenges to their career advancement …”
Section: Introductionmentioning
confidence: 99%